2015
DOI: 10.3177/jnsv.61.s112
|View full text |Cite
|
Sign up to set email alerts
|

Novel Physiological Functions of Branched-Chain Amino Acids

Abstract: Branched-chain amino acids (BCAAs: leucine, isoleucine, and valine) are nutritionally indispensable (essential) amino acids for humans. We acquire these amino acids mainly as food proteins, in which the BCAAs account for ~20% of the amino acids. The ingested BCAAs are used for protein synthesis in the body. The daily requirement for BCAAs in adults is estimated to be 85 mg/kg body weight (BW) (39, 20, and 26 mg/ kg BW for Leu, Ile, and Val, respectively) using methods such as indicator amino acid oxidation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…L-Leu is a branched chain amino acid (BCAA), and it has been demonstrated to improve muscle protein metabolism through the mTOR signaling pathway ( Shimomura et al , 2015 ). Kita et al (2015) reported that Leu in ovo injection caused an increase in the weight of whole embryos at ED 14 in layer chicks (Single Comb White Leghorn strain), in contrast with our current results in broiler chicks (Ross 308 strain).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L-Leu is a branched chain amino acid (BCAA), and it has been demonstrated to improve muscle protein metabolism through the mTOR signaling pathway ( Shimomura et al , 2015 ). Kita et al (2015) reported that Leu in ovo injection caused an increase in the weight of whole embryos at ED 14 in layer chicks (Single Comb White Leghorn strain), in contrast with our current results in broiler chicks (Ross 308 strain).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that in ovo administration of amino acids has the potential to improve post-hatch growth ( Ohta et al , 1999 ) and the feed conversion ratio ( Kadam et al , 2008 ) in neonatal chicks. L-Leu and its metabolites have been reported to suppress protein degradation and promote muscle growth ( Duan et al , 2016 ) by activating the mechanistic target of rapamycin (mTOR) signaling pathway in skeletal muscle and adipose tissues ( Shimomura et al , 2015 ). In ovo administration of L-Leu, but not L-isoleucine (L-Ile) and L-valine, on embryonic day (ED) 7 improved embryo weight on ED 14 without affecting the body weight on the hatching day ( Kita et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that, under heat conditions, fat tissue cannot be utilized as energy, and more fats would be deposited and affiliated to some organs, which may cause metabolic disturbance of stimulating lipid accumulation, increase de novo lipogenesis, and enhance amino acid catabolism for broilers . The increased concentrations of BCAAs in plasma observed on day 42 were likely a consequence of protein catabolism, and due to the transporters of amino acid were likely downregulated under heat stress condition, which might result in surplus amino acid retention and accumulation in the body. Therefore, as a compensatory or adaptation mode, the energy of the body might be redistributed by accelerating protein decomposition, with higher concentrations of the BCAAs in plasma, inducing overexpression of taste sensing receptors in the intestinal tract, which were probably inducing the satiety and inhibiting hunger feeling, finally reducing appetite.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids not only are indispensable for humans as a nutrient but also play essential roles in the control and regulation of crucial functions of the human body [12, 13]. In the brain, free amino acids are important for neurotransmission and receptor signaling pathways, and they are involved in neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%